Storytelling as a Psychoeducational Tool in Cognitive-Behavioural Therapy with Older Adults - Ondrej; Nadežda (Magyar Gerontológia, 2025)
Older adulthood is frequently accompanied by life events that threaten autonomy, safety, and personal identity, including bereavement, physical illness, accidents, or transitions in living arrangements.